The case for standalone micro-invasive glaucoma surgery: rethinking the role of surgery in the glaucoma treatment paradigm. Issue 2 (14th March 2023) - Radcliffe, Nathan
Abstract : Purpose of review: To highlight progress in glaucoma therapy challenging the traditional medication-first approach and present evidence supporting early standalone surgery in the era of micro-invasive glaucoma surgery (MIGS). Recent findings: Medical therapy is limited by well documented poor adherence that compromises the quality of intraocular pressure reduction. Results from modern clinical trials demonstrate advantages of selective laser trabeculoplasty and MIGS procedures in terms of both IOP control and progression risk. Summary: The MIGS options for pseudophakic or precataractous patients are limited by regulatory rules that require the performance of some procedures only at the time of cataract surgery. These include the iStent/iStent Inject and the Hydrus implants. Nonbleb-forming procedures currently available for standalone use in eyes with mild–moderate primary open-angle glaucoma include gonioscopy-assisted transluminal trabeculotomy (which lowers IOP by 28-61% and medication use by 38–73% in various studies), trabecular ablation with the Trabectome (23–39% and 21–43%, respectively), excisional goniotomy with the Kahook Dual Blade (15–36% and 15–40%, respectively), ab interno canaloplasty (35% and 57%, respectively), and combined canaloplasty and trabeculotomy using the OMNI system (39–40% and 64–73%, respectively). For patients who would benefit from early standalone surgery, these procedures offer meaningful reductions in both IOP and medication burden.